Pelatihan Konseling REBT Bagi Guru Bimbingan dan Konseling SMA Kota Magelang Untuk Meningkatkan Kinerja Pelayanan Konseling - Muhammad Japar; Astiwi Kurniati; Dewi Lianasari (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
The performance of counseling services is the key to the success of guidance and counseling services as a whole. To achieve success in the counseling service process, a counseling approach is needed that is tailored to the needs of learners and types of problems. To improve the performance of counseling services carried out with training activities. The purpose of this training activity is to improve the performance of teacher counseling services Guidance and Counseling through rebt counseling approach training. This activity was attended by 27 participants who joined the Teacher Consultation guidance and counseling SMA Magelang city during two days of face-to-face meetings. Based on the results of the analysis there was an increased understanding of rational Emotive Behaviour Therapy (REBT) counseling approach of the trainees with an average of 18.30%. This training has an impact for participants to apply counseling in accordance with the procedure and apply rational emotive behaviour therapy (REBT) counseling approach when providing counseling services.